Determining skeletal maturation stage using cervical vertebrae: evaluation of three diagnostic methods - Luci Mara Fachardo Jaqueira; Monica Costa Armond; Luciano José Pereira; Carlos Eduardo Pinto de Alcântara; Leandro Silva Marques (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of the present study was to compare the use of three cervical vertebral evaluation methods (Hassel-Farman, Baccetti et al., and Seedat-Forsberg) for determinating skeletal maturation stage in orthodontic patients. Twenty-three radiographs were randomly selected from a private orthodontic practice. Each radiograph was analyzed on three separate occasions by four evaluators (one radiologist and three orthodontists), who determined the skeletal maturation stage using the references established by each of the three methods. Intraevaluator and interevaluator comparisons were performed, and the degree of agreement was established using the weighted Kappa coefficient (95% CI). Good agreement (Kappa between 0.61 and 0.80) was observed between the determinations of most of the evaluators. The three methods demonstrated clinical applicability. However, the method proposed by Baccetti et al. achieved the best results, followed by the Hassel-Farman and the Seedat-Forsberg methods.